Analisis Hubungan Income Level dengan Kebiasaan Makan pada Ibu Hamil Selama Masa Pandemi Covid-19 di Wilayah Kerja Puskesmas Sukaraja Bandar Lampung - Marlina Agustina; Riska Wandini; Rilyani Rilyani (Malahayati Nursing Journal, 2023)
ABSTRACT Sukaraja Community Health Center the second place largest number of pregnant women is in Bandar Lampung City with a total of 1,127 (5.8%) after the Panjang Health Center with 1,476 (7.59%) pregnant women and in third place is the Satelit Health Center with 1,045 pregnant women (5.4%). The people in the working area of the Sukaraja Health Center have jobs 60% work as laborers, 20% as private individuals, 10% as entrepreneurs or traders, and 10% as civil servants (PNS). Income level the majority of people fall into the less due categoryincome level people less than UMR Bandar Lampung City (Rp2.770.794,14).  Known relationship income level with eating habits in pregnant women during the COVID-19 pandemic. This type of research is quantitative research with an analytical survey design approach Crossectional by distributing questionnaires about income level and Food Frequency Questionnaire (FFQ).  Frequency distribution analysis income level there are 63 (40.1%) in the sufficient category and as many as 94 (59.9%) respondents have income level  not enough. Analysis of the frequency distribution of eating habits showed that 92 (58.6%) respondents had good eating habits and 65 (41.4%) respondents had poor eating habits. Test analysis chi square on the relationship between income level with eating habits in pregnant women, with a significant valuep-value 0,000 (0,05).  This shows that there is a relationship between income level  with eating habits in pregnant women during the Covid-19 pandemic. It is expected that pregnant women can pay attention to choosing food ingredients that will be consumed during pregnancy. To meet the nutritional needs of the mother, she can carefully select food ingredients according to the level of income earned so that the nutritional needs of the mother and fetus can be met. Keywords : Income Level, Dietary Habits, Covid-19  ABSTRAK Puskesmas Sukaraja menduduki urutan kedua ibu hamil terbanyak di Kota Bandar Lampung dengan jumlah 1.127 (5,8%) setelah Puskesmas Panjang dengan jumlah ibu hamil sebanyak 1.476 (7,59%) dan diurutan ketiga adalah Puskesmas Satelit dengan ibu hamil sebanyak 1.045 (5,4%). Masyarakat di wilayah kerja Puskesmas Sukraja memiliki pekerjaan 60% bekerja sebagai buruh, 20% sebagai swasta, 10% sebagai wiraswasta atau pedagang, dan 10% sebagai pegawai negeri sipil (PNS). Income level mayoritas masyarakat masuk kedalam kategori kurang dikarenakan income level masyarakat kurang dari UMR Kota Bandar Lampung ( Rp2.770.794,14). Diketahui hubungan income level dengan kebiasaan makan pada ibu hamil selama pandemi COVID-19. Jenis penelitian ini adalah penelitian kuantitatif  dengan desain Survei Analitik pendekatan Crossectional dengan menyebarkan kuesioner tentang income level  dan Food Frequency Questionnaire (FFQ). Analisis distribusi frekuensi income level  terdapat 63 (40,1%) dalam kategori cukup dan sebanyak 94 (59,9%) responden memiliki income level kurang. Analisis distribusi frekuensi kebiasaan makan terdapat 92 (58,6%) responden memiliki kebiasaan makan yang baik dan 65 (41,4%) responden memiliki kebiasaan makan kurang  baik. Uji analisis chi-square pada hubungan antara income level dengan kebiasaan makan  pada ibu hamil, didapatkan nilai signifikasi p-value 0,000 (0,05). Hal ini menunjukkan bahwa ada hubungan antara income level  dengan kebiasaan makan pada ibu hamil selama pandemi Covid-19. Diharapkan ibu hamil untuk dapat memperhatikan dalam memilih bahan makanan yang akkan dikonsumsi selama masa kehamilan. Untuk memenuhi kebutuhan gizi ibu dapat secara cermat memilih bahan makanan sesuai dengan tingkat pendapatan yang diperoleh sehingga kebutuhan gizi ibu dan janin dapat terpenuhi. Kata Kunci : Income level, Kebiasaan Diet, Covid-19